(untitled) - Dauten, Dale (Hoboken, N.J., 2006)
With lively language and entertaining stories, (Great) Employees Only reveals how gifted bosses hire, de-hire, and inspire, and shows you how to emulate their tactics to achieve stunning success.
Keywords: Executive ability,Employee selection,Management,Khả năng điều hành,Lựa chọn nhân viên,Quản lý; Attitudes,Employees,Thái độ,Nhân viên